Triangular and single slope solar stills: Performance and yield studies with different water mass. (December 2022) - Siddula, Sundeep.; Stalin, N.; Mahesha, C.R.; Dattu, Vinjamuri S.N.C.H; S, Hemavathi; Singh, Devesh Pratap; Mohanavel, V.; Sathyamurthy, Ravishankar
Abstract: An experimental investigation on the effect of water mass on performance, and yield of a triangular slope and a typical single slope solar still is presented in this paper. The condensing cover of the triangular slope solar still is made using polyethylene, and the area of the solar still is made as 0.25 m2 for conventional and triangular slope solar still. The influencing parameters such as wind velocity, intensity, and ambient temperatures are considered, and the entire experiments were carried out during the month of December 2018 and June 2019. Furthermore, the operating parameter on the effect of the mass of water placed in both solar still is analyzed experimentally for both the solar still. The comparative analysis results revealed that the triangular single slope solar still performed better than conventional single slope solar still. The temperature of water in the basin of triangular slope solar still is 6.8 % higher as compared to conventional solar still. Also, the daily yield produced using a square basin, and triangular basin were found as 3.29 and 3.67 kg/m 2, respectively.